A cross-sectional survey on violation of cigarettes and other tobacco products act around education institutions in Puducherry - Chellamuthu, Lalithambigai; J., Jenifer Florence Mary; G., Kiruba Shankar (International Journal Of Community Medicine And Public Health, 2023)
Background: India is the second-largest tobacco consumer in the world and is responsible for around 1.3 million deaths every year. To achieve tobacco control amongst youth, it is essential that there should be strict enforcement of cigarettes and other tobacco products act (COTPA) in the vicinity of educational institutions. Objectives were to measure the violation of COTPA section 4 and 6 in Puducherry. Methods: An observational survey on COTPA violation was conducted over a period of three months in Puducherry among 300 educational institutions and tobacco point of sale (PoS). Two-stage sampling technique was used. Epicollectv5 incorporating the observational checklist was employed for data capturing and analysis was done with SPSSv24. The institute’s ethics committee approval was obtained. Results: 145 (48.3%) violated section 6b. Violation of section 6a was observed in the form of tobacco products sale by minors in 1 (0.7%) and tobacco products sale to minors in 58 (40%) amongst those 145 tobacco PoSs. Only 32 (10.7%) educational institutions complied to statutory display of “No smoking signage” board at the entrance of the educational institutions as per COTPA section 4. Active smoking was noticed within 100 meters radius in in nearly half of the institutions i.e., 133 (44.3%). Conclusions: This study showed that implementation of COTPA sections 4 and 6 in Puducherry to be deficient. It will need a concerted effort from all parties involved, including the police, educational institutions, and the local community to enforce strict implementation of the legislation for tobacco control.